Satire Language Style in Netizen Memes Against the Indonesian House of Representatives on Platform X as Social Criticism: Pragmatic Studies - Imtiyaza Nihlah Hadana; Nabila Zata Yumni; Chaerunnissa Chaerunnissa; Hoang Thi Phan (Universitas Negeri Semarang, 2026)
The development of social media has encouraged the emergence of various forms of social criticism, including increasingly creative ones, such as memes that combine visual and verbal elements. In the context of demonstrations against the 2025 DPR RI policy on platform X, memes are a means many people use to convey criticism indirectly through satirical language. This phenomenon shows a shift in the form of social criticism communication from conventional verbal expressions to multimodal digital discourses that rely on linguistic strategies and pragmatic contexts. This study aims to analyze the style of satirical language as a form of social criticism in netizens' memes against the House of Representatives of the Republic of Indonesia on platform X, using a pragmatic approach that combines pragmatic and stylistic studies, focusing on pragmatic aspects such as speech acts and situational context. Data were analyzed using qualitative descriptive methods collected through the free and capable engagement listening technique, analyzed by the referential matching method, and presented formally and informally. In this study, several memes were found that use elements of language style, such as sarcasm, irony, and metaphor, to convey social criticism subtly yet sharply, and how pragmatic contexts, such as speech and implication, strengthen satirical messages in digital discourse. The results showed that memes employ various satirical language styles, especially sarcasm, irony, metaphors, and hyperbole, to convey criticism implicitly yet sharply. Pragmatically, the meme contains expressive, representative, and directive speech, as well as unconventional implications that reinforce the message of criticism of the House of Representatives' policies and behavior. In addition, the combination of visual and verbal elements in memes has proven effective in conveying social criticism by attracting attention, making it easier to understand, and expanding the audience's reach. This research contributes to the development of pragmatic studies on digital discourse and provides an understanding of the role of memes as a medium of social criticism in contemporary social communication.